Effects of different lengths and doses of raw and treated sisal fibers in the cement composite material - Tsion Amsalu Fode; Yusufu Abeid Chande Jande; Young-Deuk Kim; Min-Gyu Ham; Jieun Lee; Thomas Kivevele; Nima Rahbar (Scientific Reports)
Abstract Sisal fiber moisture sensitivity and degradation are treated by alkaline and pozzolanic methods, such as silica fume and kaolin surface coating. However, it is novel that the treatment of sisal fiber by calcined bentonite slurry can coat sisal fiber from moisture and protect it from cement hydration by consuming free lime and reducing cement matrix alkalinity. Therefore, the present study treated sisal fibers with calcined bentonite slurry and investigated the effect of using different lengths and doses of treated and raw sisal fibers in a mortar. The results indicate that the treatment of sisal fiber with bentonite slurry improved the roughness of the fiber, reduced fresh bulk density, improved resistance in acid, salt, and alkaline conditions, and increased compressive and flexural strength at 28 and 56 days compared to the control mixture and raw sisal fiber-employed mortar. Therefore, TS1L10 improved compressive strength by 30.62% and 1.8% at 28 and 56 days, respectively. Also, TS1L10 enhanced strength and residual strength in 5% HCl by 54.54% and 72.25%, respectively, compared to the control mixture at 56 days. Generally, the present study revealed the importance of calcined bentonite-treated sisal fibers in a mortar mixture for improved durability, physical and mechanical properties.